Maternal Urinary Bisphenol A Concentration During Midterm Pregnancy and Children's Blood Pressure at Age 4. Issue 2 (February 2017) - Bae, Sanghyuk; Lim, Youn-Hee; Lee, Young Ah; Shin, Choong Ho; Oh, Se-Young; Hong, Yun-Chul
Abstract : Bisphenol A (BPA) has been reported to be associated with adverse health effects, including high blood pressure (BP). BPA is also suspected to cross placenta in pregnancy and might affect children's health. The present study was aimed to evaluate the effect of prenatal exposure to BPA on the BP of the child at the age of 4. We followed up 645 children at the age of 4 who were born from women who participated midterm during their pregnancy in a birth cohort study from August 2008 to July 2011. Because BPA and BP showed nonlinear association, we constructed a piecewise regression model to examine the association between urinary BPA concentration of mother at around 20 weeks of gestation and BP of the child at age 4 and to determine threshold level of BPA for the association. Diastolic BP of the children was positively associated with maternal urinary concentration of BPA above the threshold level measured at around 20 weeks of gestation. For 1 log unit increment of prenatal urinary BPA concentration, diastolic BP was increased by 7.9 mm Hg (SE=2.072; P =0.0001) after adjusting potential confounders. Pulse pressure was decreased by −8.0 mm Hg (SE=2.528; P =0.0015). However, systolic BP was not significantly associated with prenatal BPA concentration. The present study suggests that exposure to BPA during pregnancy is associated with higher diastolic BP of the children above a certain threshold (4.5 μg/g creatinine). Abstract : Supplemental Digital Content is available in the text.